The Effect of Incentives For Land And Building Tax on Rural and Urban Areas to Budget Solvency During Disasters in Indonesia Regencies - Made Satriawan Mahendra; Maria Tambunan; Devi Yanti Br. Bangun (Syntax Literate, 2023)
The recent publication of the World Risk Index placed Indonesia as the third country with the highest disaster risk worldwide. The valuation formulates a risk index according to the country's exposure to natural disasters and coping abilities to hazards. Indonesia is appraised as the fifth country with the highest exposure to natural disasters, with a medium coping ability. The condition could worsen if the subnational government as first responders during a disaster do not have available fiscal capacity. Indonesia's central government focuses on strengthening disaster resilience through the implementation of the Disaster Risk Financing and Insurance Strategy. One of the main strategies is to promote household insurance. However, the role of subnational government is yet to be explored. The policy alternative is to provide incentives on property taxes. This research aims to describe the correlation between property tax incentives and subnational government fiscal conditions as an answer to the possibility of using property tax incentives to promote disaster resilience while maintaining fiscal balance. The novelty of this research resides in the aggregate analysis of property tax incentives in 21 municipalities in relation to its disaster resilience policy scope. Based on the analysis, property tax stimulus is not endangering the subnational fiscal condition. Hence is a safe policy alternative to further used as a disaster resilience policy.